'I must calculate over again': measures of pain in Melville. Issue 11 (2nd November 2021) - Constantinesco, Thomas
ABSTRACT: This essay investigates the fraught question of the measure of pain in a selection of Melville's writings and examines how the articulation of pain is underwritten by a contest between the claims of arithmetic and the claims of literature. Closely reading scenes of thwarted measurements of pain in 'The Encantadas' (1854), Moby-Dick (1851), and 'Bartleby' (1853), it argues that, while the problem of pain for Melville may begin on the terrain of epistemology, it ends in the realm of literary representation, as the language of pain moves from figures to figuration.